Outlawed : Between Security and Rights in a Bolivian City - Goldstein, Daniel M., 1965- (Book collections on Project MUSE., 2012)
An ethnography examining how indigenous residents of crime-ridden, marginalized neighborhoods in Cochabamba, Bolivia, struggle to balance human rights with their need for safety and security.